Myocardial revascularization in renal transplant patients - Delgado,Daniel de Souza (2002)
OBJECTIVE: To assess the results of surgical myocardial revascularization in renal transplant patients. METHODS: From 1991 to 2000, 11 renal transplant patients, whose ages ranged from 36 to 59 (47.5±8) years, 8 males and 3 females, underwent myocardial revascularization. The time interval between renal transplantation and myocardial revascularization ranged from 25 to 120 (mean of 63.8±32.7) months. RESULTS: The in-hospital mortality rate was 9%. One patient died on the 4th postoperative day from septicemia and respiratory failure. The mean graft/patient ratio was 2.7±0.8. Only 1 patient required slow hemodialysis during 24 hours in the postoperative period, and no patient had a definitive renal lesion or lost the transplanted kidney. The actuarial survival curves after 1, 2, and 3 years were, respectively, 90.9%, 56.8%, and 56.8%. CONCLUSION: Renal transplant patients may undergo myocardial revascularization with no lesion in or loss of the transplanted kidney.